Hydrogel based on self-adaptive biological catalytic system, preparation method and application of hydrogel as dressing for wound surface of diabetes mellitus

By using hydrogel based on an adaptive biocatalytic system in diabetic wound dressings, and using dynamic adaptive mechanisms to adjust their own state, the problem that existing dressings cannot adapt to the changes in the wound microenvironment in time is solved, and efficient wound healing and reduction are achieved Effects of side effects.

CN119455068APending Publication Date: 2025-02-18EAST CHINA NORMAL UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411362842.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Diabetic wounds are difficult to heal due to complex pathological microenvironments such as hyperglycemia, hypoxia, insufficient blood vessel count, persistent inflammation, oxidative stress, etc. The existing hydrogel dressings cannot adapt to changes in the wound microenvironment in time, which can easily lead to excessive or insufficient doses. The problem.

Method used

Using hydrogels based on adaptive biocatalytic system, pH-sensitive Schiff alkaline bond crosslinks are generated by coupling oxidizing sodium alginate and gelatin, and loading glucose oxidase and catalase to construct dynamic adaptive hydrocoagulation. glue. The hydrogel can dynamically adjust its own state according to changes in the wound microenvironment and promote wound healing.

Benefits of technology

The dynamic interaction between the hydrogel and the microenvironment of diabetic wound is achieved, and its own state is adjusted according to changes in wound pH and glucose concentration, which promotes wound healing, reduces the risk of side effects, and improves the efficiency of wound repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005065364010000051
    Figure BDA0005065364010000051
  • Figure BDA0005065364010000061
    Figure BDA0005065364010000061
  • Figure BDA0005065364010000062
    Figure BDA0005065364010000062
Patent Text Reader

Abstract

The invention discloses hydrogel based on a self-adaptive biological catalysis system, a preparation method and application of the hydrogel as a diabetes wound dressing, and the preparation method of the hydrogel comprises the following steps: weighing oxidized sodium alginate, adding the oxidized sodium alginate into ultrapure water for dissolving, adding gelatin, glucose oxidase and catalase, uniformly stirring to obtain a gel solution, and carrying out freeze drying on the gel solution to obtain the hydrogel. And heating, preserving heat and standing until the gel is formed. Oxidized sodium alginate (OSA) and gelatin (GEL) are coupled to generate pH-sensitive Schiff base bond crosslinking, glucose oxidase (GOx) and catalase (CAT) are loaded in the pH-sensitive Schiff base bond crosslinking, and dynamic gel capable of interacting with the environment is prepared; the hydrogel can interact with the micro-environment (pH, glucose and the like) of the chronic wound surface of the diabetes mellitus, and can be used as a micro-environment adaptive and adjustable dressing for treating the wound surface of the diabetes mellitus.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a hydrogel based on an adaptive biocatalytic system, a preparation method and an application thereof as a diabetic wound dressing. Background Art

[0002] Diabetic wounds are a common type of chronic wounds, which usually present complex pathological microenvironments such as hyperglycemia, hypoxia, insufficient blood vessels, persistent inflammation, and oxidative stress. Diabetic wounds are usually difficult to heal due to their high-sugar environment, and wound repair has become a global challenge. Hydrogels are a type of material with a three-dimensional network structure that usually has good biocompatibility and adhesion, and can maintain the moist environment required for cell migration, effectively promoting cell proliferation and migration and the deposition of extracellular matrix, thereby promoting wound healing. The above advantages make hydrogels an ideal research material for wound dressings.

[0003] At present, there have been many studies on using hydrogels as diabetic wound dressings to promote wound healing. Starting from the reasons why diabetic wounds are difficult to recover, hydrogel dressings with anti-inflammatory, antioxidant, and angiogenesis-promoting functions have been developed. Although this type of gel can respond to and treat single or multiple stimuli in the process of wound recovery, it is still in a passive mode and cannot change in time according to the changes in stimuli. There is a risk of overdose or underdose, which can cause serious side effects and require precise monitoring to keep up with the changing wound microenvironment. To this end, there is an urgent need for adaptive hydrogels with time programmability that can adapt to the continuous changes in parameters related to the wound microenvironment during physiological processes and perform dynamic conversions. Self-regulating hydrogels can have dynamic change properties by controlling kinetic and thermodynamic equilibrium. The dynamic adaptive hydrogel constructed by this mechanism has the ability to interact with the environment and adapt to the microenvironment, and is a biomaterial that is more in line with the life form. Usually, dynamic hydrogels contain fuel-driven activation pathways and feedback-driven inactivation pathways. Under the supply of fuel, the gel precursor is activated to form a self-assembled hydrogel state. When the fuel is consumed or deactivated, it eliminates the propensity for precursor assembly, eventually leading to the disassembly of the hydrogel. Since the activation rate is much greater than the deactivation rate, the system switches from a transient assembled state to a disassembled state, allowing the regulation of its autonomous time-dependent and adaptive behavior. Summary of the invention

[0004] The purpose of the present invention is to address the above-mentioned problems and to provide a hydrogel based on an adaptive biocatalytic system, a preparation method and its application as a diabetic wound dressing.

[0005] In order to achieve its purpose, the present invention adopts the following technical solution:

[0006] The first aspect of the present invention provides a method for creating a hydrogel based on an adaptive biocatalytic system, comprising the following steps: weighing oxidized sodium alginate and adding it into ultrapure water to dissolve it, adding gelatin, glucose oxidase, and catalase, stirring evenly to obtain a gel solution, heating and keeping it warm and standing it until the gel is formed.

[0007] Preferably, the concentrations of oxidized sodium alginate, gelatin, glucose oxidase and catalase in the gel solution are respectively: 40-60 g / L, 90-160 g / L, 0.01-0.6 g / L and 0.9-1.6 mg / L.

[0008] Preferably, the concentrations of oxidized sodium alginate, gelatin, glucose oxidase and catalase in the gel solution are 50-60 g / L, 100-150 g / L, 0.05-0.4 g / L and 1.0-1.5 mg / L, respectively.

[0009] Preferably, the concentrations of oxidized sodium alginate, gelatin, glucose oxidase and catalase in the gel solution are 50-60 g / L, 100-130 g / L, 0.1-0.2 g / L and 1.1-1.3 mg / L, respectively.

[0010] Further preferably, the concentrations of oxidized sodium alginate, gelatin, glucose oxidase, and catalase in the gel solution are 50 g / L, 100 g / L, 0.1 g / L, and 1.25 mg / L, respectively.

[0011] Preferably, the preparation method comprises the following steps: weighing oxidized sodium alginate, adding it to ultrapure water and heating it to dissolve, then adding gelatin thereto and stirring, adding glucose oxidase solution and hydrogen peroxide solution during stirring, stirring evenly to obtain a gel solution, pouring it into a mold, heating and keeping it warm for 12 to 16 hours, and then forming a gel.

[0012] Preferably, the heating temperature is 35-40°C.

[0013] Preferably, the enzyme activity of the glucose oxidase is 100-250 u / mg, and the enzyme activity of the catalase is 10000-20000 u / mg.

[0014] The second aspect of the present invention provides a hydrogel based on an adaptive biocatalytic system, which is prepared by any of the methods described above.

[0015] The third aspect of the present invention provides the use of the above-mentioned hydrogel based on the adaptive biocatalytic system as a diabetic wound dressing or in the preparation of a diabetic wound dressing.

[0016] The beneficial effects of the present invention are:

[0017] The present invention provides a dynamic hydrogel that can interact with the microenvironment (pH, glucose, etc.) of a chronic wound of diabetes, as a microenvironment adaptability and regulatory dressing for treating diabetic wounds. Oxidized sodium alginate (OSA) and gelatin (GEL) are coupled to generate pH-sensitive Schiff base bond crosslinks, and glucose oxidase (GOx) and catalase (CAT) are loaded therein to prepare a dynamic gel that can interact with the environment. The alkaline environment of the chronic wound wound can be used as a fuel to activate the gelling step of the gel, thereby sealing and protecting the wound. After the gel is formed, the encapsulated GOx consumes local blood sugar to produce gluconic acid to counteract the alkaline environment, and in the process breaks the Schiff base bond to gradually dissociate the gel, forming a negative feedback loop. CAT can convert the generated hydrogen peroxide into an oxygen environment, resulting in hypoxia in the wound. The released GOx further consumes glucose in the wound, resulting in a decrease in blood sugar levels in the microenvironment, which in turn produces a series of subsequent effects - slowing down the production of acid, the recovery of the pH of the microenvironment, the degradation of the hydrogel and the slowing down of GOx release. The above process enables the gel to change its state according to the changes in the wound microenvironment and in turn regulate the microenvironment. The life of the gel can be adjusted according to the concentration of the loaded GOx, and a weaker gel can be formed during the dressing change to reduce secondary damage and better meet the needs of diabetic wound recovery. The gel's in vitro cell experiments and in vivo mouse experiments were further explored to explore the possible mechanism by which the gel promotes wound healing. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the release rate of GOx over time at different glucose concentrations.

[0019] Figure 2 The UV absorption spectra of GOx over time at different glucose concentrations: (a) glucose concentration 1 g / L; (b) glucose concentration 2 g / L; (c) glucose concentration 4 g / L.

[0020] Figure 3 This is the infrared spectrum of OSA-GEL hydrogel.

[0021] Figure 4 This is the pH change curve of the gel group with a glucose content of 1 g / L and a GOx content of 0.1 g / L.

[0022] Figure 5 This is the pH change curve of the gel group with a glucose content of 2 g / L and a GOx content of 0.1 g / L.

[0023] Figure 6 This is the pH change curve of the gel group with a glucose content of 4 g / L and a GOx content of 0.1 g / L.

[0024] Figure 7This is the pH change curve of different glucose concentrations in the gel group.

[0025] Figure 8 It is the pH change curve of different GOx concentrations in the gel group.

[0026] Fig. 9 The G' and G" data of gels with different pH values ​​as a function of frequency and time: (a) pH = 8; (b) pH = 5.

[0027] Fig.10 This is the rheological data graph of the gel dissipation cycle when the glucose concentration is 1g / L, 2g / L, and 4g / L.

[0028] Fig.11 This is the rheological data diagram of the reversible cycle characteristics of the gel when the glucose concentration is 4 g / L.

[0029] Fig.12 It is the SEM image of OSA-GEL@GC hydrogel with different dissipation cycles.

[0030] Fig.13 It is a statistical diagram of the pore size of OSA-GEL@GC hydrogel at different dissipation cycles.

[0031] Fig.14 The biocompatibility test results of the hydrogel of the present invention are shown in Figure 1, where A: cell activity data at different GOx concentrations; B: CCK-8 data at 1, 3, and 5 days when the GOx concentration is 1 μg / mL; C: confocal images of live and dead cell staining at days 1 and 3 (scale bar is 50 μm).

[0032] Fig.15 Scratch experiment of gel group and control group at 0h, 12h and 24h: (a) schematic diagram of cell migration (scale bar is 50μm); (b) statistical diagram of cell migration data.

[0033] Fig.16 Figure 1 shows the transwell experiment of the gel group and the control group at 12 h: (a) schematic diagram of cell migration (scale bar is 50 μm); (b) statistical graph of cell migration data.

[0034] Fig.17 The angiogenesis experiments of the gel group and the control group are shown: (a) Schematic diagram of 4h angiogenesis (scale bar is 50 μm); (b) Statistics of the number of tube-forming nodes; (c) Statistics of the total length of tube-forming branches.

[0035] Fig.18 The data of the polarization of induced RAW264.7 to M1 and M2 were analyzed by flow cytometry.

[0036] Fig.19Statistical analysis of RAW264.7 macrophage polarization: (a) CD86; (b) CD163.

[0037] Fig. 20 Shown are: (a) back wound recovery status of mice on days 0, 7, 14, and 21; (b) schematic diagram of back wound recovery of Group 1 (green), Group 2 (yellow), and Group 3 (orange) on day 21; (c) image of dressing during dressing change; (d) data graph of wound area changes during wound healing of Group 1, Group 2, and Group 3.

[0038] Fig.21 These are the results of H&E, Masson, and Sirius Red staining analysis, where A: H&E staining of wound tissue on day 21 (the scale bar of the first row of pictures is 50 μm, and the scale bar of the second row of pictures is 100 μm); B: Masson staining of wound tissue on day 21 (the scale bar is 100 μm); C: Sirius Red staining of wound tissue on day 21 (the scale bar is 50 μm).

[0039] Fig. 22 The results of CD 31 and α-SMA staining analysis, A: CD31 staining image of wound tissue on day 7 (scale bar is 100 μm); B: statistical graph of CD31 staining experiment on day 7; C: α-SMA staining image of wound tissue of Group 1, Group 2, Group 3 and Group 4 on day 7 (scale bar is 100 μm); D: statistical graph of α-SMA staining experiment on day 7.

[0040] Fig.23 The results of ROS clearance analysis, where A: ROS levels in the wounds of Group 1, Group 2, Group 3 and Group 4 on the 7th day (scale bar is 100 μm); B: experimental statistical chart of ROS levels in the wounds on the 7th day.

[0041] Fig.24 These are the results of the analysis of the inflammation clearance effect, where A: CD86 (green) and CD163 (red) staining experimental images in the wound surfaces of Group 1, Group 2, Group 3 and Group 4 on the 7th day (scale bar is 100 μm); B: the ratio of M1 polarization to the sum of M1 and M2 polarizations in the wound tissue on the 7th day.

[0042] Fig.25 The results of mRNA expression in wound tissue on the 7th day: (a) IL-6; (b) TNF-α; (c) IL-10. DETAILED DESCRIPTION

[0043] The present invention will be further described below in conjunction with embodiments, but the present invention is not limited thereto.

[0044] The experimental methods in the following examples are conventional methods unless otherwise specified.

[0045] Example 1

[0046] 1 Main experimental reagents and instruments

[0047] 1.1 Main experimental reagents

[0048] All drugs and reagents involved in the experiment were commercially available products purchased from Sigma-Aldrich, Anage, McLean, Bailingwei, Yuanye and other brands, and were used directly without further purification.

[0049] 1.2 Main experimental instruments

[0050] A JX-10 metal bath was used for temperature control; a LC-OES-60SH mechanical stirrer was used for stirring; a MasterTouch-Q15 water purifier was used to prepare ultrapure water; a PHS-3E pH meter was used to measure the pH value; a FD-1A-50 freeze dryer was used to freeze-dry the samples; an HRD-2 rheometer was used to test the rheological data; a Varian Cary 500 UV-visible spectrometer was used to measure the UV absorption; and an IRTrace-100 infrared spectrometer was used to measure the infrared absorption.

[0051] 2. Experimental methods - construction and performance characterization of hydrogels

[0052] 2.1 Synthesis of OSA

[0053] Weigh 1g of sodium alginate and 0.81g of sodium periodate into a 100mL ground-mouth bottle, add 10mL of ultrapure water and 10mL of ethanol to the bottle and stir the reaction for 6h at room temperature in the dark. The reason for choosing ultrapure water and ethanol in a ratio of 1:1 instead of pure water is that there are literatures showing that the pure water phase is prone to form a very viscous solution that is difficult to handle during the subsequent quenching reaction, and the addition of ethanol helps to alleviate this situation and make the reaction go more smoothly. After the reaction is completed, add 0.21mL of ethylene glycol to the bottle to quench the reaction and continue stirring for 30min. The quenched reaction solution is loaded into a dialysis bag with a molecular weight cutoff of 14000, and then the sealed dialysis bag is placed in a large beaker filled with ultrapure water for dialysis for 7 days, and the ultrapure water is replaced every 12h. After the dialysis is completed, the sample is placed in a freeze dryer for freeze drying to obtain OSA and stored in a -20℃ refrigerator.

[0054] 2.2 OSA oxidation test

[0055] 0.1 g of OSA sample was dissolved in 20 mL of 0.25 mol / L hydroxylamine hydrochloride solution and stirred for 2 h, then titrated with 0.1 M NaOH solution until the pH reached 4, which was the titration endpoint.

[0056] 2.3 Preparation of OSA-GEL@GC hydrogel

[0057] Weigh 0.025g OSA into a 5mL centrifuge tube, add 500μL ultrapure water and place in a 37℃ metal bath to dissolve. After OSA is dissolved, add 0.05g GEL and stir for 30min. During the stirring process, add GOx solution (GOx is 250u / mg) with a gel concentration of 0.1g / L and CAT solution (CAT is 20000u / mg) into the centrifuge tube, then pour into a polytetrafluoroethylene mold and stand overnight at 37℃ to obtain the molded OSA-GEL@GC hydrogel.

[0058] 2.4 GOx release rate test

[0059] A total volume of 4 mL of PBS was prepared for the control group and the experimental group. 200 μL of 10 g / L GOx solution was added to the control group, and OSA-GEL@GC hydrogel loaded with the same amount of GOx was added to the experimental group, with a gel volume of 500 μL. Different amounts of glucose were added to different experimental groups to prepare solutions of corresponding concentrations, and then the supernatant was aspirated at regular intervals for UV absorption testing.

[0060] 2.5 Infrared spectrum test

[0061] The sample to be tested is freeze-dried in advance using a freeze dryer, the sample and potassium bromide powder are ground finely and evenly in a mortar, the mixed powder is transferred to a tablet pressing mold, the powder is pressed into a thin sheet using a tablet pressing machine, the sheet is placed in the center hole of the test patch and held with a magnet, and then placed in the sample slot for infrared spectrum testing.

[0062] 2.6 pH Control Performance Test

[0063] Use a pipette to draw 10mL of PBS solution into a 20mL glass bottle, add the glucose solution prepared in advance, and then add the hydrogel loaded with the corresponding concentration of GOx. Use a pH meter to monitor the solution at regular intervals, and finally summarize it into a curve of pH change over time.

[0064] 2.7 Gelation time test

[0065] Mix and dissolve OSA and GEL according to the gel preparation method described above, and then pour the solution into a 10mL glass bottle. Tilt it at regular intervals to observe how long it takes for the gel to completely invert. The time at this time is the gelation time of the gel.

[0066] 2.8 Shape Adaptability Experiment

[0067] Prepare polytetrafluoroethylene molds of different shapes (circle, triangle, heart, square) in advance, mix OSA and GEL for 30 minutes, then pour them into the mold. After standing for a while, take out the gel from the mold and observe the gel's adaptability to different shapes.

[0068] 2.9 Dissipative cycle experiment

[0069] OSA-GEL@GC hydrogel was prepared. The GOx concentration in the gel was 0.6 g / L. When glucose solution was added to it to react, the dissipation process was carried out. After that, the rheological data of the gel was recorded with a rheometer at regular intervals. When the strength dropped to the lowest point, NaOH solution was added to it to make the overall pH to 8, which was the callback process and the rheological data of the gel was continued to be recorded. One dissipation process plus one callback process was considered as one cycle. A single dissipation cycle experiment with different glucose concentrations required adding 1 g / L, 2 g / L, and 4 g / L glucose solutions to the three groups of gels, respectively. The dissipation cycle reversible experiment selected the condition of 4 g / L glucose concentration and cycled the process three times.

[0070] 2.10 Scanning Electron Microscope (SEM) Test

[0071] Add 10mL of PBS solution with a pH of 8 to a 20mL glass bottle, add the prepared OSA-GEL@GC hydrogel, and add the coated GOx concentration of 0.6g / L. Then add glucose solution to make the glucose concentration reach 4g / L. A total of 7 groups are needed. Take out the corresponding gel when the reaction is 0h, 1h, 2h, and 3h. This process is the callback process. Add NaOH solution to the remaining groups to make the pH of the solution reach 8, and take out the corresponding gel at 5h, 7h, and 9h. This process is the dissipation process. Rinse each group of gels in ultrapure water for 3 times to remove salt particles in the gel to prevent serious discharge during shooting. After rinsing, put the gel in liquid nitrogen and freeze it for 20min. Compared with slow freezing in the refrigerator, quick freezing can better preserve the porous structure of the gel from being destroyed. After quick freezing, put the gel in a freeze dryer for freeze drying to obtain a sample that can be photographed by SEM.

[0072] 2.11 Water absorption and water retention test

[0073] Prepare 500 μL of gel sample. Weigh the initial weight of the gel using an electronic balance. Immerse the gel in 10 mL of ultrapure water. After a certain period of time, take out the gel, blot the excess water on the surface, and weigh it. When the mass no longer increases significantly, it means the gel has reached the swelling end point, i.e., the maximum water absorption rate. Take the fully swollen gel and put it into a 5 mL centrifuge tube. Place the centrifuge tube in a 37 °C metal bath and open the lid to simulate the water retention situation at the wound temperature. Record the weight of the gel at regular intervals. When the mass does not decrease significantly, it means the gel has reached the lowest water retention rate value.

[0074] 3 Experimental Results

[0075] 3.1 Degree of Oxidation Study

[0076] Sodium alginate is a natural polysaccharide extracted from brown algae. Its molecule is composed of β-D-mannuronic acid and α-L-guluronic acid. Calculating the degree of oxidation of sodium alginate can evaluate the oxidation reaction. The hydrochloric acid hydroxylamine method is used to test the degree of oxidation (DO%). Hydrochloric acid hydroxylamine can react with the aldehyde group in OSA and release hydrogen chloride, and the amount of hydrogen chloride can be titrated with NaOH solution to determine the degree of oxidation of OSA. According to the formula DO%=(198M NaOH (V sample -V control ) / m)×100. In the formula: M NaOH is the molar concentration of the NaOH solution, that is, 0.1 mol / L; V sample -V control is the volume consumption of the NaOH solution (L); m is the mass of sodium alginate (g); 198 is the molecular weight of the sodium alginate repeating unit (g / L). Finally, after measurement according to the hydrochloric acid hydroxylamine method, the DO% value of the OSA sample is 84.15%, indicating that OSA has been oxidized to a large extent and can undergo subsequent reactions with gelatin.

[0077] 3.2 Formula Optimization

[0078] 3.2.1 Gel Ratio Optimization

[0079] The rheological characterization of the gel is a classic way to measure its mechanical properties. Storage modulus (G') and loss modulus (G") are key parameters among them. Currently, it is generally considered that when G'>G", it is in the gel state; when G'<G", it is in the solution state; when G'=G", it is in the critical state between the gel and the solution. The linear viscoelastic region refers to the region where the stress and strain change linearly, and only at this time the data is physically meaningful. The linear viscoelastic region of the gel was tested and found that there was a good linear relationship between 0.1% - 10%. Subsequently, 1% was selected as the test parameter, and the data was relatively stable at this time.

[0080] In the process of Schiff base formation, OSA is responsible for providing aldehyde groups and GEL is responsible for providing amino groups. The ratio between the two will affect the generation of Schiff base. Therefore, the effect of the ratio between OSA and GEL on gel strength was investigated. The specific ratio screening and strength are shown in Table 1. According to the rheological data, it can be seen that the strength of OSA:GEL is 1:2 and 1:3 is relatively high, while the strength of 2:1 and 1:1 is low. Considering that the strength of 1:3 is not much improved compared with 1:2, 1:2 was finally selected as the subsequent experimental condition.

[0081] Table 1 Rheological data of different gel ratios

[0082]

[0083] 3.2.2 Gel concentration optimization

[0084] In addition to studying the ratio between OSA and GEL, the total gel concentration of the two was also studied. The specific concentration screening and strength are shown in Table 2. According to the rheological data, it can be seen that the gel strength of 15% and 18% is relatively high, but the improvement of 18% is not very large. Therefore, considering the raw material problem, the total gel concentration of subsequent experiments is selected as 15%.

[0085] Table 2 Rheological data of different total gel concentrations

[0086]

[0087] 3.3 GOx release rate study

[0088] In order to prove that the gel can adapt to the change of glucose, the GOx release rate of OSA-GEL@GC hydrogel under different glucose concentrations (1g / L, 2g / L, 4g / ) was tested. It is known that GOx has a specific absorption peak at 450nm, so the absorbance of this wavelength can be measured by ultraviolet absorption. According to the formula, release rate = A OSA-GEL@GC / A Control ×100% to calculate the release rate of GOx. Figure 1 and Figure 2As shown, it can be seen that when the glucose concentration is 1g / L, the final release rate of GOx is 30.6%, and the time taken to achieve this change is 24h; when the glucose concentration is 2g / L, the final release rate of GOx is 55.1%, and the time taken to achieve this change is 32h; when the glucose concentration is 4g / L, the final release rate of GOx is 61.2%, and the time taken to achieve this change is 32h. The release rate and degree of the 2g / L and 4g / L groups are much higher than that of 1g / L, while the release rate difference between 2g / L and 4g / L is not large. The reason may be that the Schiff base bond of the gel is basically broken when the pH drops to 6, which can also be seen in the subsequent pore size and strength data. When the glucose concentration is 2g / L and 4g / L, both can meet the condition of pH less than 6, so there is not much difference in the final release rate. According to the above results, it can be seen that the release degree and rate of GOx are different at different glucose concentrations, which provides a theoretical basis for the gel to adapt to microenvironments with different glucose concentrations.

[0089] 3.4 Infrared spectroscopy characterization

[0090] In order to prove that the OSA-GEL@GC hydrogel is indeed formed by Schiff base bonds rather than simple hydrogen bonds, the OSA-GEL gel was measured by infrared spectroscopy. Figure 3 It can be seen that the gel is at 1637cm -1 There is a strong absorption peak at 1640 cm-1, which is inferred to be the stretching vibration of the C=N group, proving the formation of imine bonds. -1 There is also a similar peak at 1640 cm -1 and 1543cm -1 The NH vibration peaks of amide 1 and amide 2 combined can be excluded. The above results prove the formation of Schiff base dynamic gel.

[0091] 3.5 pH control function

[0092] It is known that GOx can react with glucose to generate gluconolactone, and gluconolactone can be hydrolyzed to generate gluconic acid to reduce pH, but the specific degree and rate of pH reduction are not clear. As a dressing for diabetic wounds, it is necessary to be able to control the specific situation of pH drop so as to better adjust the content of GOx and CAT and construct a gel with controllable pH that is more suitable for actual operation. Therefore, the effects of glucose concentration and GOx concentration on pH were studied.

[0093] 3.5.1 Effect of glucose concentration on pH

[0094] First, the pH regulation ability of OSA-GEL@GC hydrogel under different glucose concentrations was studied. A total of three groups of glucose concentrations were set up, namely 1g / L (normal blood glucose concentration), 2g / L (normal blood glucose of diabetics), and 4g / L (severe blood glucose of diabetics). These three groups included blood glucose levels from normal people to different levels of blood glucose of diabetics, and the GOx concentration was selected as 0.1g / L. As shown in Table 3 and Figure 4 When the glucose concentration was 1 g / L and the GOx concentration was 0.1 g / L, the pH changed from 8 to 6.7, and the change time was 14 h; as shown in Table 4 and Figure 5 When the glucose concentration was 2 g / L and the GOx concentration was 0.1 g / L, the pH changed from 8 to 5.2, and the change time was completed in 24 h; as shown in Table 5 and Figure 6 When the glucose concentration was 4 g / L and the GOx concentration was 0.1 g / L, the pH changed from 8 to 4.5, and the change time was 24 h. The GOx concentrations of the three experimental groups were the same, and only the glucose content was different. Figure 7 It can be seen that different glucose contents in the solution will react with the GOx encapsulated in the gel. The higher the glucose content, the more acid is produced and the lower the pH is, which shows that the system can controllably adjust the range of pH changes.

[0095] Table 3 pH change data of gel group with glucose content of 1 g / L and GOx content of 0.1 g / L

[0096]

[0097] Table 4 pH change data of gel group with glucose content of 2 g / L and GOx content of 0.1 g / L

[0098]

[0099] Table 5 pH change data of gel group with glucose content of 4 g / L and GOx content of 0.1 g / L

[0100]

[0101] 3.5.2 Effect of GOx concentration on pH

[0102] Next, the pH regulation ability of OSA-GEL@GC hydrogel under different GOx concentrations was studied. A total of three groups were set up, namely 0.01g / L, 0.1g / L and 0.6g / L, and the glucose concentration was 2g / L. As shown in Table 6, when the glucose concentration was 2g / L and the GOx concentration was 0.01g / L, the pH changed from 8 to 5.2, and the change time was 108h; the data of glucose concentration of 2g / L and GOx concentration of 0.1g / L were the same as Table 4; as shown in Table 7, when the glucose concentration was 2g / L and the GOx concentration was 0.6g / L, the pH changed from 8 to 5.1, and the change time was 12h. The glucose concentrations of the three experimental groups were the same, only the GOx concentration changed. Figure 8 It can be seen that the pH of the three groups decreased from 8 to 5, indicating that the glucose concentration does determine the final acid production, that is, it controls the degree of pH decrease, and has no obvious correlation with GOx. It took 108h for the first group to reach the pH endpoint, 24h for the second group, and 12h for the third group, indicating that by controlling the concentration of GOx, the pH change range can be extended from the hour level to the day level. The dressing usually needs to be kept on the patient's wound for several days, so this also provides feasibility for subsequent dressings on organisms.

[0103] Table 6 pH change data of gel group with glucose content of 2 g / L and GOx content of 0.01 g / L

[0104]

[0105] Table 7 pH change data of gel group with glucose content of 2 g / L and GOx content of 0.6 g / L

[0106]

[0107] In order to react as quickly as possible in the dissipation behavior of the subsequent gel phase, the pH change curves of the highest concentrations of glucose and GOx, i.e., glucose concentration of 4 g / L and GOx concentration of 0.6 g / L, were studied, and the pH changed from 8 to 4.5 in 12 h.

[0108] 3.6 Gelation time and shape adaptability

[0109] If hydrogel is to be used as wound dressing, it needs to be able to gel quickly. Otherwise, considering that patients may not be able to remain still for a long time to wait for the gel to form during actual use, the gelling time of OSA-GEL@GC hydrogel was tested through a vial inversion experiment. The experiment showed that the initial state was a sol state. After intermittent tilting, it was found that the fluidity of the sol began to deteriorate after 4 minutes. After 5 minutes, it was found that the vial could be completely inverted without flowing, proving that a gel had been formed, which also showed that the gelling time of the gel was 5 minutes.

[0110] In order to be used as a wound dressing, hydrogels also need to have good shape adaptation function, because the wounds of patients are mostly irregular. If the gel does not have the shape adaptation function, on the one hand, it will not perfectly match the shape of the wound, resulting in a waste of gel and a lot of unnecessary costs. On the other hand, dressings that do not fit the wound will also be more likely to produce additional friction with the outside world, making it easier to fall off. Therefore, only gels that can adapt well to the shape of the wound have the possibility of being used as dressings. Based on this, molds with different shapes were selected to simulate irregular wounds, and then the dissolved sol was poured into the mold. The hydrogel can form squares, circles, triangles, hearts and other shapes. This also proves that the material has a strong ability in shape adaptation and can adapt well to various irregular-shaped wounds, and has the potential to be used as a wound dressing.

[0111] 3.7 Dissipative cycle performance

[0112] The gel has the function of dissipation and self-degradation, which is helpful to alleviate the problem of secondary damage caused by the dressing change process. In order to explore the dissipation and circulation characteristics of OSA-GEL@GC hydrogel, it is first necessary to prove that the strength of OSA-GEL@GC hydrogel is different under different pH conditions, that is, the strength is stronger under pH 8 and weaker under pH 5. Fig. 9 As shown in the figure, the storage modulus of the gel at pH 8 and pH 5 is greater than the loss modulus, indicating that both have formed gels, but the strength of the gel formed at pH 8 is higher than that of the gel formed at pH 5. This is also because high pH is more conducive to the formation of Schiff base bonds, thereby increasing the strength of the gel.

[0113] After proving that the gel will respond to pH in terms of strength, it is necessary to further study the state of the gel's response over time at different blood glucose concentrations. In order to explore the strength of the gel at different blood glucose concentrations, the gel was immersed in glucose solutions of different concentrations. After rheological tests such as Fig.10As shown in the figure, the storage modulus is greater than the loss modulus during the entire dissipation cycle, indicating that it is always in a gel state. When the glucose concentration is 1g / L, the gel strength decreases by 250Pa; when the glucose concentration is 2g / L, the gel strength decreases by 450Pa; when the glucose concentration is 4g / L, the gel strength decreases by 600Pa. The higher the glucose concentration, the more the gel strength decreases. This is because glucose reacts with the loaded GOx in the gel to generate gluconic acid, thereby reducing the overall pH. In previous studies, it was also found that the greater the glucose concentration, the more the pH decreases, and the more Schiff base bonds break, so the gel strength will decrease more. This shows that the gel has the ability to adapt to the wound environment. When the blood sugar concentration is high, the gel will consume more glucose, and the strength will also decrease more significantly. On the one hand, it can improve the local high-sugar environment of the wound. On the other hand, the lower gel strength can also be easier to remove when changing the dressing, thereby reducing the secondary damage caused by the dressing change and helping the recovery of the wound.

[0114] In order to truly meet the requirements of adapting to the wound microenvironment, in addition to being able to respond to different blood sugar concentrations in terms of intensity, it is also necessary to be able to resist fatigue for multiple cycles. Otherwise, the strength of the gel as a dressing will quickly drop to the minimum, and if the strength is too low, it will easily fall off and be difficult to meet the needs of daily activities. Therefore, the reversibility test of the entire dissipation and callback cycle process was continued. Fig.11 It can be seen that the gel has good fatigue resistance within 3 cycles, and there is no significant difference between the strongest and weakest points of the gel and the first cycle, which also supports the feasibility of gel materials as wound dressings.

[0115] 3.8 Study on pore size regulation of dissipative hydrogels

[0116] The gel system can change the gel state with the change of pH, which is reflected in the pore size of the gel from a microscopic perspective. The higher the pH, the more Schiff bases are generated and the tighter the cross-linking, so the pore size of the gel will be smaller. The lower the pH, the fewer Schiff bases are generated and the looser the cross-linking, so the pore size of the gel will be larger. The scanning electron microscope (SEM) can well analyze the microstructure of the gel. Fig.12 and Fig.13As shown in the figure, the strength of the gel is the weakest at 0h, and the corresponding pore size will be larger, which is 23.8μm. With the addition of alkaline buffer, the pH gradually rises. The increase in pH is conducive to the formation of Schiff base bonds, thereby increasing the bond cross-linking density. The pore size decreases to 12.3μm at 1h, 9.7μm at 2h, and finally reaches a minimum of 5.9μm at 3h. At this time, the strength of the gel is also the strongest. At this time, glucose reacts with GOx to generate acid, which causes the pH to gradually decrease. The decrease in pH will cause the Schiff base bonds to break, so the bond cross-linking density decreases and the pore size increases accordingly, which is 10.6μm at 5h, 15.9μm at 7h, and finally reaches a maximum of 22.8μm at 9h. This is also the state where the gel dissipates back to the origin with the lowest strength. SEM can help monitor the entire dissipation cycle state of the gel, which is conducive to the analysis of the entire process.

[0117] 3.9 Water absorption and water retention

[0118] The wound surface will produce a certain amount of tissue exudate, which has no effect on normal wounds. However, the wounds of diabetic patients are difficult to recover due to the high sugar environment, so tissue exudate will continue to be produced. Excessive exudate will cause the wound surface to be easily damaged and have a great impact on the patient's quality of life. As shown in Table 8, the water absorption rate of OSA-GEL@GC hydrogel can reach 150%, which can well complete the function of absorbing tissue exudate.

[0119] Table 8 Gel water absorption data statistics

[0120]

[0121] As a wound dressing, in addition to absorbing excess exudate when there is a large amount of tissue exudate, it also needs to be able to maintain a certain humidity when the wound is dry, because an overly dry environment will cause the skin's flexibility to decrease, which is not conducive to wound recovery. Therefore, a 37°C environment on the wound was simulated to test the water retention performance of the gel under this condition. As shown in Table 9, the gel reached the lowest value after 60 hours, indicating that the gel has good water retention performance and can keep the wound moist for a long time, which is conducive to wound healing.

[0122] Table 9 Gel water retention rate data statistics

[0123]

[0124] 4 Summary and Analysis

[0125] In this study, oxidized sodium alginate and gelatin were used as precursor molecules, which formed a pH-sensitive Schiff base crosslink, and loaded with GOx and CAT to construct a glucose-interactive adaptive hydrogel. The degree of oxidation of OSA was determined by the hydroxylamine hydrochloride method, proving that an oxidation reaction occurred. At the same time, the concentration and ratio of the gel were studied, and the optimal gel formula was screened out. According to the formula, the pH regulation performance of the gel was explored, and it was found that the concentrations of glucose and GOx would affect the range and time of pH change respectively. Based on this, the dissipation cycle performance of the gel was further explored, and it was found that the strength of the gel could change according to the glucose concentration, and the process could be cycled multiple times. At the same time, the pore size and GOx release rate of the dissipation cycle process were monitored by SEM and ultraviolet spectroscopy. The chemical structure of the gel was characterized by infrared, and the gelation time, shape adaptation performance and water absorption / retention rate of the gel were characterized. It was found that the gel had rapid gelation, good shape adaptation performance and water absorption / retention performance, which provided a theoretical basis for subsequent use as a dressing.

[0126] Example 2 Study on in vitro cell activity of adaptive hydrogels

[0127] 1. Biocompatibility

[0128] As a material used on living organisms, dressings must have good biocompatibility. The CCK-8 method and live-dead cell staining method were used to prove the good biocompatibility of the material in many aspects. The OSA-GEL@GC hydrogel formula used is referred to Chapter 2. Glucose oxidase reacts with glucose to produce acid and hydrogen peroxide. Although hydrogen peroxide can be reacted into water and oxygen to a certain extent by catalase, excessive acid production and residual hydrogen peroxide may be toxic to cell growth. Therefore, it is necessary to screen the safe concentration of GOx so that the appropriate GOx concentration can be used in subsequent experiments. Fig.14 As shown in A, the group without GOx was used as the 100% cell survival rate control group. When the GOx concentration was less than or equal to 10μg / mL, the cell survival rate was above 80%, indicating good biocompatibility. When the GOx concentration was 0.1μg / mL, the cell survival rate was higher than that of the control group, which may be because the oxygen produced at this time was more beneficial to cell growth than the acid produced to inhibit cells. When the GOx concentration was higher than or equal to 20μg / mL, the cell survival rate dropped to less than 10%, indicating that the amount of acid produced at this time had a significant inhibitory effect on cell growth. Therefore, the GOx concentration used in subsequent experiments should not be higher than 10μg / mL.

[0129] Since the dressing itself needs to be in contact with the wound for a long time, the toxicity within one day cannot fully explain the biocompatibility of the gel. Therefore, after selecting the appropriate GOx concentration, it is necessary to test the toxicity of the gel in long-term contact with cells. The CCK-8 data of HUVECs cells cultured for 1, 3, and 5 days with a GOx concentration of 1 μg / mL are as follows: Fig.14 As shown in B. The cell activity data of the experimental group within 5 days had no significant difference with that of the control group, proving that the gel material still has good biocompatibility in long-term cell culture.

[0130] The CCK-8 experiment can directly reflect the cell survival rate in the data, but there is no way to analyze the morphology of the cells during culture. Therefore, the live and dead cell staining experiment was further added, which can not only reflect the number of cell survival, but also analyze the cell morphology. The gel and HUVECs cells were co-cultured in a confocal dish for 1 and 3 days to demonstrate the ability of the gel to culture cells for a long time. Fig.14 As shown in Figure C, there was no significant difference in the number of cells between the control group and the experimental group on day 1 of culture, and the degree of cell spreading was good. On day 3 of culture, the number of cells in both groups increased and the cell morphology was good, proving that the gel had no inhibitory effect on cell proliferation and no significant effect on cell morphology, and had the basic properties of a wound dressing.

[0131] 2. Blood compatibility

[0132] In addition to analyzing the biocompatibility of cells, the wound dressing will come into contact with blood, so the blood compatibility of the gel also needs to be analyzed. The DDW group was used as the positive control group, and the PBS group was used as the negative control group. When red blood cells came into contact with DDW, they would rupture, causing the release of hemoglobin and other cell contents, indicating that hemolysis had occurred, while PBS would not cause red blood cells to rupture. When the gel was prepared to come into contact with red blood cells, the solution in the DDW group had clearly turned light red, while the solutions in the PBS group and the gel group were transparent. Data analysis of the optical density measured by an ELISA instrument revealed that the hemolysis rate of the gel group was less than 5%, which was considered to have good blood compatibility.

[0133] 3. Migration Capabilities

[0134] Normal cell migration is one of the important factors in the wound recovery process. Therefore, if it is to be used as a wound dressing, it must not affect the cell migration ability. Based on this, scratch experiments and transwell experiments on HUVECs cells were conducted to test the migration ability of OSA-GEL@GC gel. The first is the scratch experiment, which simulates the lateral recovery process of the wound by artificially making scratches on the overgrown monolayer of cells and observing the migration of cells to the central blank area. Fig.15 As shown in the figure, the central scratch area of ​​the control group and the gel group at 12h and 24h was smaller than that at 0h, and the reduction of the central area of ​​the gel group at 24h was more obvious than that of the control group. At 24h, the scratch area of ​​the control group was reduced to 75%, while the scratch area of ​​the gel group was reduced to 60%. Analysis by GraphPad Prism 8 software showed that there was a significant difference between the two, indicating that OSA-GEL@GC hydrogel has a certain effect in promoting two-dimensional cell migration, which may be because the hydrogen peroxide produced by the reaction of GOx and glucose is reacted by CAT into water and oxygen, and the increase of oxygen promotes the ability of cell migration.

[0135] In addition to the two-dimensional scratch test, this study also used the transwell test to further analyze the migration ability of cells. The transwell test creates a concentration difference of nutrients by adding cells and serum-free culture medium to the upper chamber and adding serum-containing culture medium to the lower chamber, thereby inducing cells to migrate from the upper layer to the lower layer, which can make up for the shortcomings of the scratch test in terms of planar migration. Fig.16 As shown in (a), after staining the cells with crystal violet, it can be seen that more cells in both the gel group and the control group passed through the small dish at 12h, and the cell morphology was also normal. Fig.16 (b) The number of cells that passed through the small dish in the two groups was counted, and it can be seen that there was no significant difference between the groups, indicating that the gel did not inhibit the normal migration of cells.

[0136] 4. Promote Angiogenesis

[0137] Wounds of diabetic patients often have insufficient angiogenesis due to the influence of high blood sugar. Blood vessels are responsible for transporting nutrients, growth factors, oxygen and other substances during wound recovery, and insufficient angiogenesis will lead to slow wound recovery or even worse. The ability of the gel to promote angiogenesis was tested by angiogenesis-promoting experiment. As shown in Figure 17(a), 4 hours after the addition of endothelial cell growth supplements, the control group had almost no vascularization due to the high-sugar environment, while the gel group had obvious angiogenesis. Fig.17 (b) and (c) are the number of nodes and total length of branches of blood vessels, respectively. It can be seen that the control group has almost no nodes and branches, while the number of nodes in the gel group reaches 160, and the total length of branches is also 2.5×104px, which is significantly different from the control group. The GOx in it can react with glucose in a high-sugar environment to reduce blood sugar concentration and generate oxygen, which shows that the group treated with gel has obvious ability to promote vascularization.

[0138] 5. Promote cell polarization

[0139] In addition to the difficulty of angiogenesis in the wounds of diabetic patients, persistent inflammation is also a major factor that hinders recovery. In the early stages of wound healing, macrophages will polarize in the M1 direction to eliminate bacteria on the wound. In the later stages of the inflammation, macrophages will normally polarize in the M2 direction to increase cell proliferation and remodeling capabilities. However, it is difficult for diabetic wounds to achieve the transition from the pro-inflammatory to the anti-inflammatory stage, which will cause excessive inflammation of the wound and make it difficult to heal. RAW 264.7 macrophages are a common inflammatory model cell. The anti-inflammatory effect of the gel can be determined by studying the differentiation of this cell. After inducing the differentiation of RAW 264.7 macrophages, the data on the polarization of the cells in the M1 and M2 directions were tested by flow cytometry. The specific results are as follows: Fig.18 CD86 and CD163 are markers of M1 and M2 macrophages, respectively. The specific data in this experiment are as follows: Fig.19 It can be seen that the expression of CD86 in the pure gel group without GOx is higher than that in the gel group with GOx, while the situation of CD163 is the opposite to that of CD86. This indicates that the differentiation of the gel group containing GOx to M2 is better than that of the gel group without GOx, which is more conducive to the development of macrophages in the anti-inflammatory direction.

[0140] After successfully constructing the required dissipative hydrogel in Example 1, this example further studied the in vitro cell activity of the gel. First, the CCK-8 toxicity experiment and the live-dead cell staining experiment proved that the gel had good biocompatibility, and the scratch experiment and the transwell experiment were used to characterize the migration ability of the cells. In the scratch experiment, the gel had a certain function of promoting cell migration, while there was no obvious adverse effect in the transwell experiment. Through the vascularization experiment, it can be clearly seen that the gel can promote tube formation, and after inducing the differentiation of RAW 264.7 macrophages, the differentiation was monitored by flow cytometry. It was found that the cells in the OSA-GEL@GC group were more inclined to M2 differentiation, while the control group was more inclined to M1 differentiation, which also illustrates the ability of the gel to promote the production of anti-inflammatory factors. The above results show that OSA-GEL@GC gel has the function of optimizing and regulating the behavior of some cells without affecting the normal cell growth process, laying a solid foundation for the next step of living wound dressing research.

[0141] Example 3 Study on the wound repair effect of the adaptive hydrogel of the present invention

[0142] 1 Experimental methods

[0143] 1.1 Construction and repair of diabetic wound model

[0144] Type 1 diabetes mouse model: All animal experiments were approved by the Animal Ethics Committee of the Ninth People's Hospital Affiliated to Shanghai Jiao Tong University. Male C57BL / 6J mice weighing about 25 g were fasted for 12 hours and then intraperitoneally injected with streptozotocin (STZ) 80-160 mg / kg. In the following seven days, the blood glucose level in the tail vein blood was randomly measured three times. If the random blood glucose was continuously higher than 16.7 mmol / L, the diabetic model was considered to be successfully established. After the model was successfully established, the mouse back skin was wounded, the mice were anesthetized with isoflurane, the hair on the back of the mice was shaved, and a circular complete skin wound with a diameter of 6 mm was cut without connecting the fascia carnosus muscle. The circular ring was sutured at the wound to prevent the wound from healing by skin muscle contraction. Normal mice and diabetic mice were randomly divided into three groups: the first group only applied TegadermTM transparent dressing on the wound; the second group applied transparent dressing after adding pure gel without GOx to the wound; the third group applied transparent dressing after adding OSA-GEL@GC gel containing GOx to the wound. To ensure the effective concentration of GOx and CAT in the gel, the gel dressing was changed every 2-3 days. The wound size was measured on days 0, 7, 14, and 21, and analyzed using ImageJ 2.1.0 software.

[0145] 1.2 Monitoring of glucose concentration in wound surface

[0146] 20 mg of wound tissue was collected from the diabetic group, and blood was collected on the 7th and 14th days. The tissue was placed in 200 μL of PBS and ground at 2500r for 10 min in a high-throughput tissue grinder at 4°C. The concentrations of glucose and protein in the supernatant were determined using a glucose kit and a BCA protein detection kit, respectively. The amount of glucose per gram of protein was considered to be the glucose concentration in the tissue.

[0147] 1.3 Wound histology and immunohistochemistry studies

[0148] Mice were euthanized at the planned time, and the regenerated wound skin was obtained by dissection. The skin samples were divided into 3 groups. A part was taken out and fixed in 4% paraformaldehyde solution and stored in a refrigerator at 4℃ for 24h. After embedding with paraffin, the wound skin tissue was cut into 5μm sections. Hematoxylin and eosin (H&E), Masson trichrome (Masson) and Sirius Red staining were used to detect the degree of epithelial healing, fibroblast distribution and collagen deposition during wound healing. CD31 antibody, α-smooth muscle actin (α-SMA), CD86 and CD163 were used to detect the vascularization, wound contraction and verification of the wound on the 7th day. The primary antibodies for immunofluorescence were CD31 antibody, α-SMA antibody, FITC anti-mouse CD86 antibody and CD163 antibody. The secondary antibodies for immunofluorescence were FITC-conjugated antibodies or cy3-conjugated antibodies. The cell nuclei were stained with 4',6-diamino-2-phenylindole (DAPI). Confocal microscopy was used to image and observe five random viewpoints of each section. Some fresh skin tissue samples were embedded in the optimal storage temperature composite material and sectioned at 8 μm. The level of ROS in the wound tissue was detected by dihydroethidium red fluorescence staining kit. After washing with PBS, the samples were incubated with 2.5 μmol / L dihydroethidium solution at 37°C for 30 min, and the cell nuclei were stained with DAPI. Confocal microscopy was used to image and observe five random viewpoints of each specimen. Tissue RNA was extracted from the remaining fresh specimens to detect the levels of inflammatory regulators interleukin (IL)-6, tumor necrosis factor (TNF)-α, and IL-10 in the regenerated wound tissue. After grinding with a high-throughput tissue grinder, the RNA in the wound tissue was extracted and purified by the TRIzol method. The cDNA was synthesized using the reverse transcription reagent PrimeScript RT Reagent Kit. Gene expression was detected by quantitative real-time polymerase chain reaction (qRT-PCR) on the real-time fluorescence quantitative PCR system QuantStudio 3 and the highly specific dye quantitative PCR detection kit SYBR Green PCRMix Kit. The target gene primers are shown in Table 4.2. Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) was used as the internal reference. The relative expression level of the target gene mRNA was calculated using the 2-△△Ct method and normalized with the expression level of the control group to calculate the fold change.

[0149] 2 Results

[0150] 2.1 Analysis of wound repair effect

[0151] After verifying the feasibility of the preliminary materials and the preliminary effect of promoting healing by in vitro cells, OSA-GEL@GC hydrogel was further applied to the mouse model to observe whether it could promote wound healing in vivo. Type 1 diabetic mice were induced by continuous intraperitoneal injection of STZ. The model was considered to be successfully established when the random blood glucose was higher than 16.7mmol / L within 7 days. After that, a wound with a diameter of 6mm was made on the back of the mouse and the dressing was changed every 2-3 days until all mice were killed on the 21st day. The mice were divided into a diabetic group (DB) and a normal mouse group (NM). Each group was further divided into 3 groups, namely, the Tegaderm group with only transparent TegadermTM; the pure gel OSA-GEL group without GOx and CAT; and the complete gel OSA-GEL@GC group containing GOx and CAT. The above six groups were arranged in sequence, namely Group 1: DB Tegaderm, Group 2: DB OSA-GEL, Group 3: DBOSA-GEL@GC, Group 4: NM Tegaderm, Group 5: NM OSA-GEL, and Group 6: NM OSA-GEL@GC.

[0152] like Fig. 20 As shown in (a), the wounds on the back of mice were photographed regularly to observe the healing status of each group. From the comparison between Group 1 and Group 4, it can be seen that the wound healing rate of diabetic mice was lower than that of normal mice when only the transparent TegadermTM was applied. The wounds of the normal mice group had basically healed on the 21st day, while the diabetic mice still had wounds on the 21st day, indicating that the high-sugar environment of diabetic mice does slow down the recovery of wounds. From the comparison between Group 1, Group 2 and Group 3, it can be seen that Group 1 still had a large wound on the 21st day, Group 2 also had a wound but it was smaller than that of Group 1, and the wound of Group 3 had basically healed, with only a small area of ​​wound, some of which were yellow and were new granulation tissue. A certain amount of granulation tissue can promote wound healing.

[0153] Fig. 20(b) is a schematic diagram of the back wound recovery of Group 1 (green), Group 2 (yellow) and Group 3 (orange) on the 21st day, which can more intuitively show the changes in the direct wound area of ​​the three groups. This shows that OSA-GEL itself can better protect the wound, and the hydrogel material itself has a porous structure. Chapter 2 also proved that the gel has good water absorption / retention capacity, so it can absorb tissue exudate and ensure a certain humidity of the wound to promote wound recovery. The complete OSA-GEL@GC gel can better promote wound healing, because the GOx and CAT contained in the gel can consume glucose to reduce blood sugar concentration and produce oxygen to promote wound healing.

[0154] like Fig. 20 As shown in (c), when changing the dressing, the wound can be seen through the dressing of Group 3, but not of Group 2. This indicates that the strength and thickness of the gel decrease after dissipation, so it is easier to stick less when changing the dressing, which can reduce the secondary damage caused by the dressing change. Fig. 20 In (b), Group 4, Group 5, and Group 6 are compared, and it can be seen that the recovery speed and trend of the three groups are basically the same. On the 14th day, a small area of ​​wound surface remains, and on the 21st day, it is basically completely recovered. This is because normal mice are not in a high-sugar environment and the wound recovery speed is fast. Therefore, the gel did not play a significant role in promoting recovery during the entire recovery process. Fig. 20 (d) The data showed a more intuitive change in wound area of ​​Group 1, Group 2, and Group 3 during the entire wound recovery period. On the 21st day, the wound area of ​​Group 1 was 28%, that of Group 2 was 18%, and that of Group 3 was only 5%. GraphPad Prism analysis showed significant differences among the three groups, further proving that OSA-GEL@GC hydrogel can promote wound recovery in vivo.

[0155] 2.2 Glucose concentration analysis

[0156] The main reason why diabetic patients' wounds are difficult to recover is that high blood sugar concentration leads to a series of problems such as insufficient angiogenesis, persistent inflammation and oxidative stress. The GOx added to the gel has the ability to consume glucose. The glucose concentration of the wound surface of Group 1, Group 2 and Group 3 on the 7th day was measured by a glucose kit to test the ability of the gel to reduce blood sugar concentration in vivo. On the 7th day, the blood sugar concentration of Group 1 was 0.43mmol / g, the blood sugar concentration of Group 2 was 0.37mmol / g, and the blood sugar concentration of Group 3 was 0.26mmol / g. The blood sugar concentration of Group 3 was significantly lower than that of the other two groups, while there was no significant difference between the blood sugar concentrations of Group 1 and Group 2, which shows that OSA-GEL@GC hydrogel does have the effect of reducing blood sugar concentration in vivo and promoting wound healing.

[0157] 2.3 H&E, Masson, and Sirius Red staining analysis

[0158] Although the wound recovery changes can be observed intuitively through the wound picture, it is difficult to analyze the reasons for wound healing from a more microscopic perspective. The wound was further analyzed through H&E, Masson, and Sirius Red staining of the wound tissue. Based on the previous wound recovery conditions, the gel had no obvious effect on wound recovery in the normal mouse group. Therefore, in the following analysis, the diabetic mouse group and the normal mouse control group were mainly analyzed, namely Group 1, Group 2, Group 3, and Group 4. H&E staining can stain tissues well with hematoxylin and eosin stains to analyze the degree of wound epithelial healing. Hematoxylin stain is alkaline and can dye the chromatin in the cell nucleus and the nucleic acid in the cytoplasm purple or blue, while eosin stain is acidic and can dye the extracellular matrix, cytoplasm, etc. red or pink. Such as Fig.21 As shown in A, the epithelial tissue of Group 4, as a normal mouse group, is continuous, while the epithelial tissue of Group 1 and Group 2 is not continuous. Compared with Group 1, Group 2 has more epithelial migration, while the epithelial tissue of Group 3 is continuous and the collagen arrangement in the dermis is denser. In addition, the number of myofibroblasts in Group 3 is lower than that in Group 1 and Group 2. When the wound is basically healed, myofibroblasts will transform into fibroblasts. These results show that the wounds of Group 3 have basically healed, while the wounds of Group 1 and Group 2 are still in the contraction healing stage.

[0159] Masson staining is a classic collagen staining method, in which low molecular weight dyes can penetrate low permeability and dense structure tissues, while high molecular weight dyes can only enter high permeability and loose structure tissues. The molecular weight of light green or aniline blue is relatively large, making collagen fibers blue or green and muscle fibers red, so it is very good to distinguish collagen fibers from muscle fibers. Fig.21 As shown in Figure B, the collagen arrangement of Group 1 and Group 2 was slightly disordered or sparse, with more myofibroblasts, while the collagen arrangement of Group 3 was more regular and dense, with fewer myofibroblasts, which was consistent with the results of H&E staining, indicating that the wounds of Group 1 and Group 2 were still in the contraction healing stage, while the wounds of Group 3 had basically healed.

[0160] Sirius Red staining is a good way to observe the collagen content. Collagen is usually alkaline, and Sirius Red is a strong acidic dye, so it can react strongly with collagen to produce obvious birefringence, in which collagen appears yellow. Fig.21 As shown in Figure C, the collagen in Group 1 is very sparse, while the collagen content in Group 2 and Group 3 is relatively high, which also indicates that the wound healing effect of Group 2 and Group 3 will be better. The above three staining methods can prove that the wound recovery degree of Group 3 is better than that of Group 2, and Group 2 is better than Group 1, indicating that OSA-GEL without GOx can promote the recovery of mouse wounds, and OSA-GEL@GC hydrogel can accelerate the epithelialization and collagen deposition of wounds, and the effect of promoting wound recovery is the best.

[0161] 2.4CD31 and α-SMA staining analysis

[0162] Insufficient angiogenesis in diabetic patients limits the delivery of nutrients and growth factors, which is a serious problem for wound healing. Therefore, the gel was studied to see if it could promote angiogenesis in wounds in vivo. CD31 can be used to mark endothelial cells. Fig. 22 A, The pink part is the blood vessels. Group 4 has the largest number of blood vessels. Group 3 has more blood vessels than Group 2, and Group 2 has more blood vessels than Group 1. The difference between the number of blood vessels in Group 3 and that in Group 1 of normal mice is not much. Fig. 22 B is a statistical graph of the CD31 staining results. It can be seen more intuitively from the data that there are significant differences between the groups and Group 3 has the highest value among the three groups of diabetic mice, indicating that OSA-GEL@GC hydrogel can indeed promote angiogenesis.

[0163] In the early stage of wound healing, the more myofibroblasts there are in the dermis, the stronger the conduction ability of wound healing is. Therefore, α-SMA is used to mark myofibroblasts. Fig. 22 C and 22D, the number of myofibroblasts in Group 4 is the largest, the number of positive cells in Group 3 is more than that in Group 2, and Group 2 is more than Group 1, which indicates that the number of myofibroblasts in Group 3 is the largest and can contract the wound more quickly in the early stage of wound healing.

[0164] 2.5 Analysis of ROS removal effect

[0165] A certain amount of ROS can achieve a sterilizing effect and promote wound tissue recovery, but the ROS level in diabetic wounds will be higher than the activity of antioxidant enzymes, leading to oxidative stress. Excessive ROS levels will promote the expression of inflammatory factors, form persistent inflammation, accelerate cell aging and affect collagen synthesis. The ROS level of tissue sections in each experimental group on the 7th day was detected by dihydroethidium red fluorescence staining kit. Fig.23 As shown in A and 23B, the red fluorescent staining part reflects the ROS level of each group. Group 4 is the normal mouse group, in which the red fluorescent part is very small, while the ROS level of Group 2 is 3 times that of Group 4, the ROS level of Group 2 is less than that of Group 1, and that of Group 3 is less than that of Group 2. This shows that OSA-GEL@GC hydrogel can reduce the production of ROS in tissues by lowering blood sugar.

[0166] 2.6 Analysis of inflammation clearance effect

[0167] Persistent inflammation is one of the important reasons why diabetic wounds are difficult to heal. In the early stages, proinflammatory cytokines can cause inflammation of the wound. At this time, immune cells will engulf invading pathogens and clean the wound. In the later stages of inflammation, proinflammatory cytokines will turn to anti-inflammatory direction. However, repeated tissue damage in chronic wounds of diabetic patients will lead to persistent inflammation and excessive inflammatory response, which will cause a counter-effect and delay wound healing. CD86 and CD163 co-staining is used to mark M1 and M2 macrophages to determine the level of inflammation. M1 cells have a pro-inflammatory effect, while M2 cells have an anti-inflammatory effect. Fig.24As shown in A and 24B, the proportion of M1 cells in Group 4 as the normal mouse group to the total number of M1 and M2 cells was only 0.10, the proportion of Group 1 was 0.76, the proportion of Group 2 was 0.52, and the proportion of Group 3 was 0.25. Anti-inflammatory results showed that the macrophages in the group with OSA-GEL@GC hydrogel were less polarized in the M1 direction and more polarized in the M2 direction, indicating that OSA-GEL@GC hydrogel can promote the transformation of macrophages from pro-inflammatory to anti-inflammatory.

[0168] In addition to co-staining of wound tissues with CD86 and CD163, the expression levels of inflammatory factors in fresh wounds on day 7 were also detected by RNA extraction and qPCR. Both IL-6 and TNF-α are pro-inflammatory cytokines, such as Fig.25 As shown in (a) and (b), the expression levels of IL-6 and TNF-α in Group 4 were both 1, 9.06 and 4.21 in Group 1, 2.7 and 1.98 in Group 2, and 1.81 and 1.56 in Group 3. The expression of these two factors in Group 3 was lower than that in Group 2, and that in Group 2 was lower than that in Group 1. IL-10 is an anti-inflammatory cytokine. Fig.25 As shown in (c), the IL-10 expression level of Group 4 is 1, Group 1 is 0.3, Group 2 is 0.38, and Group 3 is 0.43. The expression level trend of IL-10 is exactly opposite to the previous trend of pro-inflammatory cytokines. Overall, it shows that OSA-GEL can reduce the inflammation level of the wound to a certain extent, and OSA-GEL@GC has the best effect on reducing the inflammation level of the wound.

[0169] 3 Summary

[0170] This example further verifies the effect of OSA-GEL@GC hydrogel in wound healing in vivo. First, diabetic mice were successfully induced by the STZ method, and then a control group, an OSA-GEL group without GOx, and an OSA-GEL@GC group containing GOx were set up respectively. Normal mice were also divided into these three groups. Through regular photography observations, it was found that the OSA-GEL@GC group had the best wound recovery among the three groups of diabetic mice, followed by OSA-GEL, and finally the control group, while there was no obvious difference in the normal mouse group. Therefore, the three groups of diabetic mice and the normal mouse control group were further explored. By detecting the glucose content in the wound, it was found that OSA-GEL@GC hydrogel has the function of local hypoglycemia in the wound. At the same time, H&E, Masson and Sirius Red staining of the wound tissue found that the gel can promote wound re-epithelialization and collagen deposition. CD31 and α-SMA staining found that the gel has the performance of promoting wound angiogenesis and early wound contraction and healing, and dihydroethidium staining was used to characterize the gel's ability to promote the removal of ROS. Finally, the wound was stained with CD86 and CD163, and the expression of IL-6, TNF-α, and IL-10 inflammatory factors in mRNA was statistically analyzed, proving that the gel has the function of reducing the level of tissue inflammation. The above results prove that the gel can promote the healing of diabetic wounds through the mechanisms of lowering blood sugar, promoting angiogenesis, clearing ROS, and reducing inflammation levels.

Claims

1. A method for creating a hydrogel based on an adaptive biocatalytic system, characterized in that: The method comprises the following steps: weighing oxidized sodium alginate and adding it into ultrapure water to dissolve it, adding gelatin, glucose oxidase and catalase, stirring evenly to obtain a gel solution, heating and keeping the solution warm to stand until the gel is formed.

2. The method according to claim 1, characterized in that: The concentrations of oxidized sodium alginate, gelatin, glucose oxidase and catalase in the gel solution are 40-60 g / L, 90-160 g / L, 0.01-0.6 g / L and 0.9-1.6 mg / L respectively.

3. The method according to claim 1, characterized in that: The concentrations of oxidized sodium alginate, gelatin, glucose oxidase and catalase in the gel solution are 50-60 g / L, 100-150 g / L, 0.05-0.4 g / L and 1.0-1.5 mg / L respectively.

4. The method according to claim 1, characterized in that: The concentrations of oxidized sodium alginate, gelatin, glucose oxidase and catalase in the gel solution are 50-60 g / L, 100-130 g / L, 0.1-0.2 g / L and 1.1-1.3 mg / L respectively.

5. The method according to claim 1, characterized in that: The concentrations of oxidized sodium alginate, gelatin, glucose oxidase and catalase in the gel solution are 50 g / L, 100 g / L, 0.1 g / L and 1.25 mg / L respectively.

6. The method according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: weighing oxidized sodium alginate, adding it into ultrapure water, heating and dissolving it, then adding gelatin into the water and stirring it, adding glucose oxidase solution and hydrogen peroxide solution during the stirring process, stirring evenly to obtain a gel solution, pouring the solution into a mold, heating and keeping the solution warm for 12 to 16 hours, and then forming a gel.

7. The method according to any one of claims 1 to 5, characterized in that: The heating temperature is 35-40°C.

8. The method according to any one of claims 1 to 5, characterized in that: The enzyme activity of the glucose oxidase is 100-250 u / mg, and the enzyme activity of the catalase is 10000-20000 u / mg.

9. A hydrogel based on an adaptive biocatalytic system, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the hydrogel based on the adaptive biocatalytic system according to claim 9 as a diabetic wound dressing or in the preparation of a diabetic wound dressing.

Citation Information

Cited By

  • Blood glucose response type hydrogel

    CN120983700A